(untitled) (Bangladesh Journal of Zoology, 2015)
Landing of vulnerable ray species, Leopard whip ray, Himantura undulata (Bleeker, 1852) was recorded from two fish landing centers of Bangladesh Fisheris Development Corporation. The highest landing volume was recorded 0.420 mt in March 2010 and the lowest 0.112 mt in August 2011. Average highest and lowest landings were 52.5 kg and 2.88 kg in the months of November2012 and in March 2009 respectively. During 2009-2010 H. undulata contributed only 0.560 MT (0.33 %) followed by 2010-2011, 2011-2012 and 2012- 2013 period were 0.893 MT (0.28%), 0.882 MT (0.23% ) and 0.434MT (0.12%) of the year wise total landing volume of sharks and rays respectively. Month wise maximum and minimum recorded numbers of landed H. undulata were 59 and 4 in the month of November, 2012 and July, 2009 respectively. The highest and lowest percentage contributions were 2.54% and 0.28% in July, 2009 and March, 2013 respectively. Bangladesh J. Zool. 42(1): 11-17, 2014